Analisis Wacana Kritis Model Sara Mills dalam Novel Sunyi Di Dada Sumirah Karya Artie Ahmad - Erantika, Dewi Erawati; Asnawi, Asnawi (UIR PRESS, 2021)
Sunyi di Dada Sumirah is a novel by Artie Ahmad which tells of three different periods of having to live their destiny in their own silence, while injustice continues to accompany their steps. This research discusses the injustice of women in the novel Sunyi di Dada Sumirah by Artie Ahmad using the Sara Mills model of critical discourse analysis. There are various kinds of gender discussions, starting from the feelings of men or women, as well as the injustice or discrimination that women receive themselves. Thus, in the novel it is also necessary to carry out critical discourse analysis. Based on this background, the problem formulation in this thesis is How are women viewed from the position of the subject-object in Artie Ahmad's novel Sunyi Di Dalam Dada Sumirah? How are women viewed from the reader's position in Artie Ahmad's novel Sunyi Di Dalam Dada Sumirah?. The method used in this research is qualitative content analysis. This method is commonly used to understand symbolic messages from a discourse or text. This research is viewed from the subject-object position and the reader's position. The purpose of this research is to describe, analyze, identify, interpret and conclude the position of the subject-object and the reader in describing women in the novel Sunyi di Dada Sumirah by Artie Ahmad. The results of this study concluded that even though the women who were the subjects suffered, the portrayal of women in the novel was still biased. In this novek woman is still depicted as a weak figure, unable to fight back when she gets acts of violence, her position is under men or someone in power and often becomes the object of male exploitation.